ECCO2R in 12 COVID-19 ARDS Patients With Extremely Low Compliance and Refractory Hypercapnia - Ding, Xin; Chen, Huan; Zhao, Hua; Zhang, Hongmin; He, Huaiwu; Cheng, Wei; Wang, Chunyao; Jiang, Wei; Ma, Jie; Qin, Yan; Liu, Zhengyin; Wang, Jinglan; et al. (Frontiers in Medicine, 2021)
Purpose: A phenotype of COVID-19 ARDS patients with extremely low compliance and refractory hypercapnia was found in our ICU. In the context of limited number of ECMO machines, feasibility of a low-flow extracorporeal carbon dioxide removal (ECCO2R) based on the renal replacement therapy (RRT) platform in these patients were assessed. Methods: Single center, prospective study. Refractory hypercapnia patients with COVID-19 associated ARDS were included and divided into adjusted group and unadjusted group according to the level of PaCO2 after the application of ECCO2R system. Ventilation parameters (tidal volume (VT), respiratory rate, PEEP), platform pressure (Pplat) and driving pressure (DP), respiratory system compliance, arterial blood gases, and ECCO2R -system characteristics were collected. Results: Twelve patients with refractory hypercapnia were enrolled and the PaCO2 was 64.5[56-88.75] mmHg. In the adjusted group, VT were significantly reduced from 5.90±0.16 to 5.08±0.43 ml/kg PBW, DP and Pplat were also significantly reduced from 23.5± 2.72 mmHg and 29.88±3.04mmHg to 18.5±2.62mmHg and 24.75±3.41mmHg separately. And in the unadjusted group, PaCO2 decreased from 94[86.25, 100.3] mmHg to 80[67.50,85.25] mmHg but with no significant difference, and the DP and Pplat weren’t decreased after weighing the pros and cons. Conclusions: A low-flow ECCO2R system based on the RRT platform enabled CO2 removal and could also decrease the DP and Pplat significantly, which provided a new way to treat these COVID-19 ARDS patients with refractory hypercapnia and extremely low compliance.